Faktor-faktor Yang Menyebabkan Perilaku Agresif pada Anak Usia Dini Studi di Taman Kanak-Kanak Azharyah Palembang - Mu’aimadillah, Mu’aimadillah (Indonesian Research Journal on Education, 2022)
A good kindergarten education, of course, is undergoing learning activity programs and must pay attention to factors so that the development of children's potential can be stimulated to the fullest. To provide developmental stimulation in children, 4 areas must be assessed, namely gross motor, fine motor, social language skills, and daily life. This research is classified as Qualitative research with a case study approach. Case studies are part of a research methodology in which aresearcher is required to be more careful, thorough, and in-depth. Researchers analyze data that has been obtained from the field. Data analysis is the process of coding and compiling prepared interview transcripts. Research data obtained through observations and interviews conducted during research at Azharyah Kindergarten Palembang began when making observations to obtain data obtained by presenting questions that had been prepared in advance according to research needs.